Dictionary of pharmaceutical medicine - Nahler, Gerhard (Springer ; ECPM, European Center of Pharmaceutical Medicine, 2017)
This dictionary details various terms typically used in pharmaceutical medicine. It also explains commonly used abbreviations.
Keywords: Pharmacy -- Dictionaries.; Pharmacy -- Acronyms -- Dictionaries.; elektronické knihy; electronic books